RABINDRANATH TAGORE AND JAMES HENRY COUSINS a conversation in letters. - Tagore, Rabindranath, 1861-1941; Cousins, James Henry, 1873-1956; Majumdar, Sirshendu ([S.l.] : ROUTLEDGE, 2021)
This book presents a set of original letters exchanged between Rabindranath Tagore, the first Asian to win the Nobel Prize for Literature, and the eminent Irish poet and theosophist, James Henry Cousins. Through these letters, the volume explores their shared ideas of culture, art, aesthetics, and education in India; aspects of Irish Orientalism; Irish literary revival; theosophy, eastern knowledge, and spiritualism; cross-cultural dialogue and friendship; Renaissance in India; anti-imperialism; nationalism; internationalism; and cosmopolitanism. The book reveals a hitherto unexplored facet concerning two leading thinkers in the history of ideas in a transnational context. With its lucid style, extensive annotations and a comprehensive Introduction, this book will be an essential read for scholars and researchers of Indian literature, Bengali literature, comparative literature, South Asian studies, Tagore studies, modern Indian history, philosophy, cultural studies, education, political studies, postcolonial studies, India studies, Irish history, and Irish literature. It will also interest general readers and the Bengali diaspora.
Keywords: LITERARY COLLECTIONS / General; SOCIAL SCIENCE / General; Tagore, Rabindranath, -- 1861-1941 -- Correspondence; Cousins, James Henry, -- 1873-1956 -- Correspondence; Tagore, Rabindranath, -- 1861-1941 -- Friends and associates